Comprehensive manual therapy for the lumbar spine on DVD - Kostopoulos, Dimitrios; Rizopoulos, Konstantine; Slack Incorporated (Thorofare, NJ : SLACK, 2004)
Lumbar topics include: herniated disc-radiculopathy, sprains and strains, lumbar spinal stenosis.
Dimitrios Kostopoulos, Konstantine Rizopoulos.
Keywords: Low Back Pain -- therapy; Lumbosacral Region -- physiopathology; Manipulation, Spinal -- methods